A parallel volume of fluid-Lagrangian Parcel Tracking coupling procedure for diesel spray modelling. (3rd June 2017) - Yu, H.; Goldsworthy, L.; Ghiji, M.; Brandner, P.A.; Garaniya, V.
Highlights: A parallel VOF-LPT coupling procedure for complete spray simulation. Characteristics of the in-nozzle flow phenomena. Analysis of primary and secondary diesel atomisation. Abstract: A parallel computing Eulerian/Lagrangian multi-scale coupling procedure for diesel spray simulation is presented. Early breakup of the diesel jet is captured by using a compressible Volume of Fluid (VOF) method. In regions where the phase interface can no longer be sufficiently resolved, separated and small scale liquid structures are described by a Lagrangian Parcel Tracking (LPT) approach, in conjunction with secondary breakup modelling and a turbulence stochastic dispersion model. The coupling of these two descriptions utilises a Region Coupling Method and an efficiently parallelised droplet identification and extraction procedure. This approach enables run-time VOF-LPT field coupling and filters small-scale liquid structures that are suitable candidates for Eulerian-liquid-structure/Lagrangian droplet conversion, preserving their position, mass and momentum. The coupling procedure is initially applied to model the atomisation of a simple liquid jet and the results are compared with that of a statistical coupling approach to demonstrate the performance of the developed coupling procedure. Its application is then extended to simulate a real diesel spray from a nozzle with a sharp entrance. Coupling in-nozzle phenomena such as flow separation, flow detachment and turbulence to the primary and secondary spray atomisation, provides a tool for the prediction of complex spray dynamics.